On the quantum theory of light interacting with nano-materials - Mansuripur, Masud (SPIE, 2023)
The fundamental processes of absorption, stimulated and spontaneous emission, and elastic as well as inelastic scattering involving light and atoms, molecules, and nano-particles have been studied for decades using both classical and quantum theories. While providing an overview of the subject, this paper presents a streamlined approach to studying atom-photon interactions in the context of modern quantum optics in the hope of providing guidance for applications in the general area of molecular and nano-photonic machines.